Role of vitamin D in formation of vertebral pain in women in postmenopausal period depending of bone mineral density - Povorozniuk, Vladyslav; Orlik, Tatyana; Balatska, Nataliya; Mutz, V. (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2015)
Objective: To investigate the relationship between the level of 25(OH)D in blood serum and characteristics of vertebral pain in older women depending on the bone mineral density (BMD). Methods: The study involved 178 postmenopausal women aged from 50 to 79 years. Patients were divided into groups depending on the level of 25 (OH) D in blood serum (less than 25, 25–50, 50 nmol/l) and BMD (osteoporosis, osteopenia, norm). Vertebral pain was assessed with using of a visual analog scale. Level 25(OH)D in the blood serum was analyzed by elektrokhemiluminiscent method. BMD was measured at the lumbar spine (LI–LIV) using dual-energy X-ray densitometer. Results: It was found that the frequency and intensity of pain in the thoracic spine in women of older age groups with different state of BMD (osteoporosis, osteopenia, the norm) does not depend on the level of 25(OH)D in blood serum. Frequency of pain in the lumbar spine is significantly higher in patients with low levels of 25(OH)D in blood serum (deficiency and insufficiency) regardless of BMD state. Decreasing of BMD indicators (osteoporosis and osteopenia) do not change the risk of vertebral pain against the background of the unsatisfactory status of vitamin D but increase its expression in the lumbar spine. Conclusion: The expression of lumbar spine pain in older women with systemic osteoporosis and osteopenia linked to the level of 25(OH)D in blood serum which substantiate the feasibility of its screening examination in this category of patients.